ANALISA PENGARUH PERTUMBUHAN PENJUALAN DAN AKTIVA LANCAR TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA (BEI) Ã¢â‚¬Â - Meti Zuliyana (Fakultas Ekonomi Universitas Tridinanti Palembang, 2014)
The capital market is anÃ‚Â appropriateÃ‚Â representation for assessing the condition of the company - a company in a country because almost all industries are representedÃ‚Â in itÃ‚Â andÃ‚Â one of the effective meansÃ‚Â toÃ‚Â accelerateÃ‚Â theÃ‚Â developmentÃ‚Â of aÃ‚Â countryÃ‚Â andÃ‚Â the development of capital markets provide a source of investmentÃ‚Â forÃ‚Â investors.Ã‚Â OneÃ‚Â activity is to investÃ‚Â inÃ‚Â companiesÃ‚Â issuingÃ‚Â shares. ToÃ‚Â investÃ‚Â inÃ‚Â sharesÃ‚Â ofÃ‚Â analysisÃ‚Â needed toÃ‚Â measureÃ‚Â the valueÃ‚Â ofÃ‚Â shares,Ã‚Â namelyÃ‚Â fundamental analysis and technical analysis. The Ã‚Â Ã‚Â purposeÃ‚Â ofÃ‚Â thisÃ‚Â studyÃ‚Â Ã‚Â wasÃ‚Â to Ã‚Â determineÃ‚Â Ã‚Â InfluenceÃ‚Â SalesÃ‚Â Growth Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â ( Sales Growth )Ã‚Â And Ã‚Â Ã‚Â AssetsÃ‚Â Ã‚Â On Ã‚Â Ã‚Â StockÃ‚Â Ã‚Â PriceÃ‚Â Ã‚Â OnÃ‚Â ConsumerÃ‚Â GoodsÃ‚Â Industry Company In Indonesia Stock Exchange (IDX). Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â This study used secondary data obtained from the annual financial statements published by the Indonesia Stock Exchange (IDX) using a sample of 12 consumer goods industry during the period 2006-2009. For analysis and hypothesis testing used multiple regression analysis model by using SPSS version 16.0. From the results of the study by using a multiple linear regression showed that in partial sales growth (Sales Growth) t value of -0.122 <t table value of 1.679 with a significance level of more than 0.05 is 0.904. While the variable current assets (Current Assets) t value of -0.222 <t table value of 1.679 with a significance level of more than 0.05 is 0.825, the variable sales growth (Sales Growth) and current assets have no significant effect terhada stock prices, whereas in simultaneously throughout the company's fundamentals: sales growth (Sales Growth) and current assets have a significant effect on stock prices with a level of significance (0.05). Instead, in this study can cover all companies listed on the Indonesia Stock Exchange and more attention to factors - external factors (inflation, exchange rate movements of currencies, interest rates, political conditions) and expectations (regional economic conditions) that more has influence on stock prices. Keywords: Stock price, Sales Growth (Sales Growth), Current Assets.